PARTISIPASI MASYARAKAT DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KECAMATAN SUMEDANG SELATAN - Fepi Febianti (JRPA - Journal of Regional Public Administration, 2019)
This study aims to analyze the problem: Community Participation in Rural and Urban Land and Building Tax (PBB-P2) payments in South Sumedang District. The method used in the preparation of this proposal is a Qualitative Research Method, with an independent variable namely Community Participation. The informants were as many as 4 people, namely the sub-district head, the head of the governance section, the UN collector, and the village head. Based on the results of interviews and data analysis, it was concluded that community participation in the payment of land and building taxes in rural and urban sectors in South Sumedang District can be said to be quite good. Constraints contained in the Land and Building Tax Payment in rural and urban sectors in the Sumedang Selatan Subdistrict are weak personal awareness, lack of information, lack of free time, and economic capacity of the community. Efforts to overcome these problems are conducting intensive socialization to the public, and the existence of clarity of information by providing online services